2017
DOI: 10.1371/journal.pone.0174476
|View full text |Cite
|
Sign up to set email alerts
|

Expression of claudin-11, -23 in different gastric tissues and its relationship with the risk and prognosis of gastric cancer

Abstract: Claudins play an important role in regulating the permeability of epithelial and endothelial cells and in the maintenance of cell polarity. We aimed to investigate expression of claudin-11, -23 in different gastric tissues and its relationship with clinicopathologic parameters and prognosis of gastric cancer. We compared their expression levels in the paired cancerous tissues versus those in the adjacent noncancerous tissues by real-time PCR, western blotting and immunohistochemistry. The results showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In addition, the expression of claudin-10 and claudin-17 was downregulated, while the expression of claudin-14 was upregulated, in gastric cancer tissues compared with in tumor adjacent tissues ( 48 ). The expression of claudin-11 and −23 was greatly increased in paracancerous gastric tissue compared with cancerous tissue ( 49 ). These results suggested that the functions of claudin proteins may be highly tissue-specific and may be the candidate biomarkers of gastric cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of claudin-10 and claudin-17 was downregulated, while the expression of claudin-14 was upregulated, in gastric cancer tissues compared with in tumor adjacent tissues ( 48 ). The expression of claudin-11 and −23 was greatly increased in paracancerous gastric tissue compared with cancerous tissue ( 49 ). These results suggested that the functions of claudin proteins may be highly tissue-specific and may be the candidate biomarkers of gastric cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, expression of CLDN11 and CLDN23 is downregulated in gastric cancer89 and miR-421 was implicated in regulating CLDN11 expression to promote the proliferation, invasion and metastasis of gastric cancer cells90 (table 2). In contrast, CLDN23 positive expression was associated with poor prognostic outcomes of patients with gastric cancer and may therefore serve as an independent predictor of patient survival.…”
Section: Tj Proteins and The Gi Tractmentioning
confidence: 99%
“…Whether GSTP1 and CLDNs playing significant roles in different biological characteristics of cancers is not clear, we hypothesize that there may be a close correlation in activity/function between CLDNs and GSTP1, which may provide a possible direction for cancer chemotherapy. Recently a study confirmed CLDN23 as a potential biomarker for the diagnosis and prognosis of gastric cancer, and it was further demonstrated that CLDN23 expression was positively correlated with GSTP1 activity in gastric cancer [ 19 ]. Abnormal high CLDN6 expression was found in MCF-7/MDR multidrug resistant breast cancer cells, however whether CLDN6 confers resistance to various anti-cancer drugs in this cell line need to be explored.…”
Section: Introductionmentioning
confidence: 99%